Effects and Mechanism of Combinational Chemical Agents on Solution‐Derived K0.5Na0.5NbO3 Piezoelectric Thin Films. Issue 5 (7th February 2016) - Wang, Yumei; Yao, Kui; Sharifzadeh Mirshekarloo, Meysam; Tay, Francis Eng Hock
Abstract : Sodium potassium niobate (KNN) piezoelectric ceramic thin films were prepared by a chemical solution deposition method, in which the introduction of appropriately combinational organic stabilizing agents, including monoethanolamine (MEA), diethanolamine (DEA), and ethylenediaminetetraacetic acid (EDTA), dramatically suppressed the volatile loss of the alkali ions, improved the crystallinity, and promoted crystal orientation of the perovskite phase in the resulting KNN thin films. Theoretical analyses including ab initio calculation based on molecular model indicated that stronger binding structure could form comprising the alkali ions and the combinational EDTA‐(DEA‐MEA) chemical agents than the cases of using individual binding agents separately. Outstandingly large effective piezoelectric strain coefficient d 33 under the substrate clamping condition was achieved. The theoretical and experimental results provide the insight on the underlying interaction mechanism between the multiple stabilizing chemical agents and metal ions, and the guidance for establishing the methodology for producing high quality oxide thin films from chemical solutions with dedicatedly designed combinational stabilizing agents.